Hybrid Precoding With Rate and Coverage Constraints for Wideband Massive MIMO Systems - Kong, Lingxiao; Han, Shengqian; Yang, Chenyang (IEEE transactions on wireless communications, 2018)
Hybrid architecture is recognized as complexity and cost effective for the implementation of massive multi-input multi-output (MIMO) systems, where analog precoder is used to form narrow beams toward users for data transmission with reduced number of radio frequency chains. However, besides transmitting the user-specific data, the system also needs to broadcast control signaling intended for all users simultaneously, which requires wide beams to ensure the coverage. In this paper, we study hybrid precoder design for downlink space-division multiaccess and orthogonal frequency-division multiplexing wideband massive MIMO systems, aimed at minimizing the total transmit power of the base station, subject to both the coverage constraint of signaling and data rate requirements of users. We first derive the coverage probability of massive MIMO systems with hybrid architecture under general spatially correlated channels, based on which an alternating optimization algorithm and a low-complexity algorithm with channel statistics based analog precoder are, respectively, proposed to optimize the hybrid precoder. Simulation results show the performance gain of the proposed hybrid precoder over the method that only considers data rate requirements or coverage constraints and also demonstrate the necessity of separating data and signaling planes at high frequencies.